"Superaerophobic" NiCo bimetallic phosphides for highly efficient hydrogen evolution reaction electrocatalysts. Issue 50 (28th May 2021) - Zhang, Ling; Huang, Jiawei; Zheng, Qizheng; Li, Ang; Li, Xianglan; Li, Jing; Shao, Minhua; Chen, Hongmei; Wei, Zidong; Deng, Zihua; Li, Cunpu
Abstract : A "superaerophobic" NiCo bimetallic phosphide electrocatalyst has been fabricated by employing bimetal–organic frameworks as self-sacrificing templates. Abstract : A "superaerophobic" NiCo bimetallic phosphide electrocatalyst has been fabricated by employing bimetal–organic frameworks as self-sacrificing templates. An overpotential of only 205 mV can drive the HER current density to 800 mA cm −2, which is even superior to that for Pt/C. This study provides a promising approach for the development of industrialized HER electrocatalysts.